Placental insufficiency in women with gestational hypertension: the role of endothelial dysfunction - Sokolovska, I. S.; Nakonechnyi, S.; Соколовська, Ірина Сергіївна; Наконечний, Сергій Юрійович (Liverpool : Cognum Publishing House, 2023)
The development of gestational hypertension in women in the second half of pregnancy is accompanied by endothelial dysfunction with an increase in the level of von Willebrand factor, the development of hemodynamic disorders, ultrasound signs of placental insufficiency, fetal hypoxia with the development of fetal growth restriction syndrome.
Keywords: placental insufficiency; endothelial dysfunction; gestational hypertension